School Vouchers Italian Style - Giorgio Brunello; Daniele Checchi (Institute for the Study of Labor (IZA), 2005)
School vouchers introduced recently in some Italian regions have lowered the cost of private schools. On one side, we provide evidence that Italian private schools may be selected for different reasons than quality considerations. On the other side, by exploiting individual data on voucher applicants, we present evidence that the percentage of voucher applicants is higher the higher the average quality of private schools, which we explain with the fact that better quality schools provide better services to students, including information and consulting on vouchers. We show that enrolment in private schools responds sluggishly to changes in tuition induced by vouchers. Under stringent assumptions, we estimate the slopes of demand and supply of private education in the largest Italian region, Lombardy, during the first two years since implementation of a voucher scheme, and provide a quantitative assessment of the long-term impact of vouchers on tuition fees and enrolment in private schools.
Keywords: I22; 330; school vouchers; Italy; Schule; Voucher; Privatschule; Schulpolitik; Italien